(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to identify the concept of financial and monetary policies and sustainable development, and then measure and analyze the extent of the impact of these policy tools on the goals of sustainable development in Iraq during the period (2015-2023).The variables (public revenues, public expenditures, exchange rates, interest rates) were taken as independent variables, while the percentage of achievement of the second and fifth goals of the sustainable development goals in Iraq during the period (2015-2023) was taken. The research started from the hypothesis that (there is a direct impact of financial and monetary policy tools on some sustainable development goals in Iraq during the period (2015-2023). In order to prove this hypothesis, the descriptive (theoretical) method and the quantitative method were combined using the statistical program (EVIEWSE 12). The research reached a set of recommendations, most notably (the lack of a direct impact of financial and monetary policy tools on some sustainable development goals in Iraq during the period (2015-2023). The research also recommended a set of recommendations, the most important of which is (the need for financial policy tools (public expenditures and public revenues) to be directed to support the goals and directions of sustainable development in Iraq, by directing public expenditures for infrastructure and revitalizing the economy in its various sectors and not limited to the government sector only, and this is what ensures achieving growth in the gross domestic product, which is one of the most important goals of sustainable development).